Production method of LC-grade diethyltoluenediamine
By using immobilized ionic liquid Lewis acid catalyst and composite gas in DETDA production, gentle pressurization reactions are carried out, which solves the problem of many side reactions and difficult catalyst reuse in the existing process, and achieves high-purity and low by-product DETDA production.
Patent Information
- Application Number
- CN202510336213.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-21
AI Technical Summary
The existing DETDA production process conditions are harsh, resulting in many side reactions, low product purity, and difficult to separate and reuse the catalyst.
Under the protection of inert gas, toluene diamine and a specially made immobilized ionic liquid Lewis acid catalyst were mixed, ethylene and composite gas were introduced, and a gentle pressurization reaction was carried out, and the material liquid was then refined to obtain a high-purity LC-grade diethyl toluene diamine.
DETDA production with few side reactions, high product yield and high purity is achieved. The catalyst is easy to separate and reuse multiple times, and is suitable for industrial applications.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic chemistry, and in particular to a method for producing LC-grade diethyltoluenediamine. Background Art
[0002] Diethyltoluenediamine, referred to as DETDA, is a low-viscosity, non-toxic, odorless light yellow liquid. It is mainly used in the fields of chain extenders for polyurethane and polyurea elastomers, polyurethane and epoxy resin curing agents, coatings, lubricants, industrial oil antioxidants, chemical synthesis intermediates, etc. Commercialized DETDA is a mixture of 3,5-diethyl-2,4-toluenediamine (about 80%) and 3,5-diethyl-2,6-toluenediamine (about 20%).
[0003] DETDA is usually prepared from toluenediamine (TDA) and ethylene as raw materials. In the presence of a catalyst, a Friedel-Crafts alkylation reaction occurs under high temperature and high pressure conditions to obtain crude DETDA. The catalyst is further separated and removed, and pure DETDA is obtained by distillation. The reaction is as follows: .
[0004] The key to this reaction is the catalyst, which must provide a certain Lewis acidity to promote the alkylation of the benzene ring. Considering factors such as production cost, operational stability, and especially reaction effect, the current large-scale production of DETDA generally uses aluminum powder, zinc powder and / or AlCl3 as catalysts, but the process conditions are extremely harsh, with the reaction temperature usually as high as 200-300°C and the reaction pressure up to 50MPa. Although the harsh process conditions are conducive to the polarization of ethylene, so that it reacts with toluenediamine to form DETDA, they also increase the possibility of DETDA further reacting with ethylene to form triethyltoluenediamine (ETDA); and excessively high temperature and pressure will promote the occurrence of a large number of side reactions, such as the demethylation and deamination reactions of toluenediamine, and these demethylation and deamination products will continue to react with ethylene to generate a large number of ethylated by-products; in addition, Lewis acid can also promote the occurrence of N-alkylation reactions on the benzene ring, resulting in a large number of N-alkylation substituted by-products of toluenediamine. Therefore, how to avoid the occurrence of side reactions and promote the reaction to DETDA has become the key to improving the efficiency of the alkylation reaction of toluenediamine.
[0005] Chinese invention patent CN106083605B discloses a method for synthesizing diethyltoluenediamine, which forms an "aromatic amine-aluminum" catalyst system with diaminotoluene under certain conditions, and then undergoes an alkylation reaction with ethylene in an autoclave. After the reaction is completed, it is directly distilled in a distillation kettle, and the intercepted front fraction and the remaining catalyst system are directly returned to the autoclave, and then the raw material diaminotoluene is added to directly undergo an alkylation reaction with ethylene. After the "aromatic amine-aluminum" catalyst system is prepared once, it can be reused. However, the catalytic efficiency of the catalyst system is not high. Summary of the invention
[0006] The invention aims to provide a method for producing LC-grade diethyltoluenediamine. The method is simple, has few side reactions, high product yield, high purity, is easy to realize industrial application, has a wide source of raw materials, mild reaction conditions, and a catalyst that is easy to separate and can be reused multiple times, and has broad application prospects.
[0007] The technical solution of the present invention is achieved in this way: The invention provides a production method of LC-grade diethyltoluenediamine, comprising the following steps: under the protection of inert gas, mixing toluenediamine and a catalyst, heating and stirring, introducing ethylene and a composite gas at the same time, keeping the temperature and pressurizing for reaction, cooling, releasing the pressure, discharging the material, and refining the liquid to obtain LC-grade diethyltoluenediamine.
[0008] As a further improvement of the present invention, the temperature is raised to 160-180°C, the pressure of the heat preservation and pressurization reaction is 6-7MPa, and the time is 2-4h. The composite gas includes an inert gas, a protonic acid gas and an ammonia gas in a volume ratio of 7-10:3-5:1-3. The protonic acid gas is selected from at least one of hydrogen fluoride, hydrogen chloride, hydrogen bromide, hydrogen iodide, hydrogen sulfide, and fluorosilicic acid gas. The ammonia gas is selected from at least one of ammonia, monomethylamine, dimethylamine, trimethylamine, and triethylamine gas.
[0009] As a further improvement of the present invention, the added amount of the catalyst is 0.5-10wt% of toluenediamine, preferably 0.5-1.5wt%. The preparation method of the catalyst is as follows: S1. Adding zirconium tetrachloride to a mixed solvent of N,N-dimethylformamide and acetic acid, adding 2-aminoterephthalic acid, hydrothermally reacting, centrifuging, washing, and drying to obtain UiO-66-NH2; S2. piperazine and dibromo-p-xylene were mixed and added to acetonitrile, and the mixture was heated under reflux under inert gas protection, centrifuged, washed, and dried to obtain compound 1; S3. Compound 1 is added to a solvent, 1,3-propane sultone is added, the temperature is raised, the reaction is performed by centrifugation, washing, and drying to obtain compound 2; S4. Compound 2 was added to water, methanesulfonic acid was added, the reaction was heated and stirred, the solvent was removed under reduced pressure, washed with ether, and dried to obtain an ionic liquid; S5. The ionic liquid and UiO-66-NH2 were mixed, ground, heated for polymerization reaction, the product was extracted with acetonitrile, washed with methanol, centrifuged, and dried to obtain a composite; S6. The complex is added to an aqueous solution of aluminum salt and zinc salt, the reaction is stirred, centrifuged, washed, and dried to obtain an Al / Zn-loaded complex; S7. Adding the Al / Zn composite to an aqueous solution of cerium salt, impregnating, centrifuging, washing, and drying to obtain a catalyst.
[0010] As a further improvement of the present invention, the volume ratio of N,N-dimethylformamide and acetic acid in the mixed solvent of N,N-dimethylformamide and acetic acid in step S1 is 35:2-4, the mass ratio of zirconium tetrachloride and 2-aminoterephthalic acid is 14-17:12-14, the temperature of the hydrothermal reaction is 120-130°C, and the time is 20-24h.
[0011] As a further improvement of the present invention, the molar ratio of piperazine to dibromoparaxylene in step S2 is 1:1-1.1, and the heating reflux reaction time is 24-30 hours.
[0012] As a further improvement of the present invention, in step S3, the mass ratio of the compound 1 to 1,3-propane sultone is 20-22:24-26, the temperature of the temperature-raising reaction is 55-65° C., and the time is 2-4 h.
[0013] As a further improvement of the present invention, in step S4, the mass ratio of compound 2 to methanesulfonic acid is 45-47:20-22, the temperature of the heating and stirring reaction is 75-85° C., and the time is 7-10 h.
[0014] As a further improvement of the present invention, in step S5, the mass ratio of the ionic liquid to UiO-66-NH2 is 7-10:12-15, the grinding time is 1-3 hours, and the temperature of the heating polymerization reaction is 65-75°C for 24-30 hours.
[0015] As a further improvement of the present invention, the mass ratio of the composite, aluminum salt and zinc salt in step S6 is 10:3-5:1-2, the aluminum salt is selected from at least one of aluminum sulfate and aluminum nitrate, the zinc salt is selected from at least one of zinc chloride, zinc sulfate and zinc nitrate, and the stirring reaction time is 30-50min; the mass ratio of the Al / Zn-loaded composite and cerium salt in step S7 is 100:3-5, the impregnation time is 10-12h, and the cerium salt is cerium chloride or cerium nitrate.
[0016] The present invention further protects a catalyst, the preparation method of which comprises the following steps: S1. Add 1.4-1.7 parts by weight of zirconium tetrachloride to a mixed solvent of N,N-dimethylformamide and acetic acid, add 1.2-1.4 parts by weight of 2-aminoterephthalic acid, hydrothermally react at 120-130°C for 20-24h, centrifuge, wash, and dry to obtain UiO-66-NH2; The volume ratio of N,N-dimethylformamide to acetic acid in the mixed solvent of N,N-dimethylformamide and acetic acid is 35:2-4; S2. 10 mmol piperazine and 10-11 mmol dibromo-p-xylene were mixed and added to acetonitrile, and the mixture was heated under reflux under inert gas protection for 24-30 h, centrifuged, washed, and dried to obtain compound 1; S3. Add 2-2.2 parts by weight of compound 1 to ethanol, add 2.4-2.6 parts by weight of 1,3-propane sultone, raise the temperature to 55-65° C., stir the reaction for 2-4 hours, centrifuge, wash, and dry to obtain compound 2; S4. 4.5-4.7 parts by weight of compound 2 was added to water, 2-2.2 parts by weight of methanesulfonic acid was added, heated to 75-85°C, stirred for reaction for 7-10h, the solvent was removed under reduced pressure, washed with ether, and dried to obtain an ionic liquid; S5. 0.7-1 parts by weight of the ionic liquid and 1.2-1.5 parts by weight of UiO-66-NH2 were mixed, ground for 1-3 hours, heated to 65-75°C, polymerized for 24-30 hours, extracted with acetonitrile, washed with methanol, centrifuged, and dried to obtain a composite; S6. The composite was added to 1 part by weight of an aqueous solution containing 0.3-0.5 parts by weight of an aluminum salt and 0.1-0.2 parts by weight of a zinc salt, the reaction was stirred for 30-50 min, centrifuged, washed, and dried to obtain an Al / Zn composite; S7. Add 1 part by weight of the Al / Zn-loaded composite into an aqueous solution containing 0.03-0.05 parts by weight of a cerium salt, immerse for 10-12 hours, centrifuge, wash, and dry to obtain a catalyst.
[0017] The present invention has the following beneficial effects: The present invention prepares an immobilized ionic liquid Lewis acid catalyst. First, piperazine and dibromo-p-xylene are reacted, and then reacted with 1,3-propane sultone to obtain a polyionic liquid precursor, which is reacted with methanesulfonic acid to prepare a polyionic liquid. This sulfonic acid group (-SO3H) functionalized acidic ionic liquid is an emerging catalyst. It has both the high activity of liquid acid and the separability of solid acid. Compared with traditional acids (sulfuric acid or hydrochloric acid), it has the advantages of high acidity, high catalytic activity, environmental friendliness and recyclability. Ionic liquids have physical and chemical properties such as high adsorption capacity, high activity, good thermodynamic stability and high solubility. The anions and cations of ionic liquids have the characteristics of designability and easy directional functionalization. However, they have the disadvantages of being difficult to separate from homogeneous catalytic reaction systems and difficult to reuse. In addition, low molecular weight ionic liquids are difficult to separate during the preparation process and have low catalytic activity. Therefore, the present invention prepares a polyionic liquid and carries out in-situ polymerization with the polyionic liquid and the MOFs material (UiO-66-NH2). The MOFs material has the characteristics of high specific surface area, adjustable structural pore size, easy functionalization, etc., and the polyionic liquid prepared by the present invention with high acidity is loaded on the surface of the alkaline MOFs material. On the one hand, the two can be loaded through reaction with a high loading amount, and on the other hand, the acidity can be adjusted to achieve a suitable acid-catalyzed neutral activity, thereby greatly improving the catalytic activity, and it is easy to realize the directional reaction of TDA and ethylene to obtain diethyltoluenediamine, which greatly reduces the occurrence of side reactions and improves the yield of diethyltoluenediamine, thereby greatly improving the economic value of the reaction.
[0018] The reaction is as follows: ; The prepared composite is loaded with copper and zinc, which greatly improves the catalytic activity and has a synergistic catalytic effect. It is further impregnated with cerium ions for doping. The rare earth cerium ions have an unfilled 4f electron layer structure, produce very rich electronic energy levels, and have a relatively large ion radius, just like adding "industrial MSG". More new catalytic active centers will be generated, thereby greatly improving the catalytic activity.
[0019] The production method of LC-grade diethyltoluenediamine provided by the invention is simple, has few side reactions, high product yield, high purity, is easy to realize industrial application, has wide raw material sources, mild reaction conditions, and the catalyst is easy to separate and can be repeatedly utilized, thus having broad application prospects. DETAILED DESCRIPTION
[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Preparation Example 1 Preparation of Catalyst Here’s how: S1. Add 1.4 g zirconium tetrachloride to 300 mL of a mixed solvent of N,N-dimethylformamide and acetic acid, add 1.2 g 2-aminoterephthalic acid, hydrothermally react at 120° C. for 20 h, centrifuge, wash, and dry to obtain UiO-66-NH2; the volume ratio of N,N-dimethylformamide to acetic acid in the mixed solvent of N,N-dimethylformamide and acetic acid is 35:2; S2. 10 mmol piperazine and 10 mmol dibromo-p-xylene were mixed and added to 50 mL acetonitrile. The mixture was heated under reflux for 24 h under nitrogen protection, centrifuged, washed, and dried to obtain compound 1. S3. Add 2 g of compound 1 to 200 mL of ethanol, add 2.4 g of 1,3-propane sultone, heat to 55° C., stir to react for 2 h, centrifuge, wash, and dry to obtain compound 2; S4. Add 4.5 g of compound 2 to 200 mL of water, add 2 g of methanesulfonic acid, heat to 75 ° C, stir and react for 7 h, remove the solvent under reduced pressure, wash with ether, and dry to obtain an ionic liquid; S5. 0.7 g of ionic liquid and 1.2 g of UiO-66-NH2 were mixed, ground for 1 h, heated to 65 ° C, polymerized for 24 h, extracted with acetonitrile, washed with methanol, centrifuged, and dried to obtain a composite; S6. 1 g of the complex was added to 50 mL of an aqueous solution containing 0.3 gl of aluminum sulfate and 0.1 g of zinc chloride, and the reaction was stirred for 30 min, centrifuged, washed, and dried to obtain an Al / Zn-loaded complex; S7. Add 1 g of the Al / Zn composite into 50 mL of an aqueous solution containing 0.03 g of cerium chloride, immerse for 10 h, centrifuge, wash, and dry to obtain a catalyst.
[0022] Preparation Example 2 Preparation of Catalyst Here’s how: S1. Add 1.7 g zirconium tetrachloride to 300 mL of a mixed solvent of N,N-dimethylformamide and acetic acid, add 1.4 g 2-aminoterephthalic acid, hydrothermally react at 130° C. for 24 h, centrifuge, wash, and dry to obtain UiO-66-NH2; the volume ratio of N,N-dimethylformamide to acetic acid in the mixed solvent of N,N-dimethylformamide and acetic acid is 35:4; S2. 10 mmol piperazine and 11 mmol dibromo-p-xylene were mixed and added to 50 mL acetonitrile. The mixture was heated under reflux for 30 h under nitrogen protection, centrifuged, washed, and dried to obtain compound 1. S3. Add 2.2 g of compound 1 to 200 mL of ethanol, add 2.6 g of 1,3-propane sultone, heat to 65° C., stir to react for 4 h, centrifuge, wash, and dry to obtain compound 2; S4. Add 4.7 g of compound 2 to 200 mL of water, add 2.2 g of methanesulfonic acid, heat to 85 ° C, stir and react for 10 h, remove the solvent under reduced pressure, wash with ether, and dry to obtain an ionic liquid; S5. 1 g of ionic liquid and 1.5 g of UiO-66-NH2 were mixed, ground for 3 h, heated to 75 ° C, polymerized for 30 h, extracted with acetonitrile, washed with methanol, centrifuged, and dried to obtain a composite; S6. 1 g of the complex was added to 50 mL of an aqueous solution containing 0.5 g of aluminum sulfate and 0.2 g of zinc sulfate, and the reaction was stirred for 50 min, centrifuged, washed, and dried to obtain an Al / Zn-loaded complex; S7. Add 1 g of the Al / Zn composite into 50 mL of an aqueous solution containing 0.05 g of cerium chloride, immerse for 12 h, centrifuge, wash, and dry to obtain a catalyst.
[0023] Preparation Example 3 Preparation of Catalyst Here’s how: S1. Add 1.55 g zirconium tetrachloride to 300 mL of a mixed solvent of N,N-dimethylformamide and acetic acid, add 1.3 g 2-aminoterephthalic acid, hydrothermally react at 125° C. for 22 h, centrifuge, wash, and dry to obtain UiO-66-NH2; the volume ratio of N,N-dimethylformamide to acetic acid in the mixed solvent of N,N-dimethylformamide and acetic acid is 35:3; S2. 10 mmol piperazine and 10.5 mmol dibromo-p-xylene were mixed and added to 50 mL acetonitrile. The mixture was heated under reflux for 27 h under nitrogen protection, centrifuged, washed, and dried to obtain compound 1. S3. 2.1 g of compound 1 was added to 200 mL of ethanol, and 2.5 g of 1,3-propane sultone was added, the temperature was raised to 60° C., the reaction was stirred for 3 h, centrifuged, washed, and dried to obtain compound 2; S4. Add 4.6 g of compound 2 to 200 mL of water, add 2.1 g of methanesulfonic acid, heat to 80 ° C, stir and react for 8 h, remove the solvent under reduced pressure, wash with ether, and dry to obtain an ionic liquid; The results of infrared spectrum analysis are as follows: -1 These peaks are related to the stretching vibration of -CH and -CN on the piperazine ring, 1188 and 1022 cm -1 The characteristic peaks are attributed to the S=O and SO stretching vibrations of the -SO3H group.
[0024] S5. 0.85 g of ionic liquid and 1.35 g of UiO-66-NH2 were mixed, ground for 2 h, heated to 70 ° C, polymerized for 27 h, extracted with acetonitrile, washed with methanol, centrifuged, and dried to obtain a composite; S6. 1 g of the complex was added to 50 mL of an aqueous solution containing 0.4 g of aluminum nitrate and 0.15 g of zinc nitrate, and the reaction was stirred for 40 min, centrifuged, washed, and dried to obtain an Al / Zn-loaded complex; S7. 1 g of the Al / Zn composite was added to 50 mL of an aqueous solution containing 0.04 g of cerium nitrate, immersed for 11 h, centrifuged, washed, and dried to obtain a catalyst.
[0025] Comparative Preparation Example 1 Compared with Preparation Example 3, the difference is that the ionic liquid in step S4 is replaced by 1-butyl-3-(4-sulfobutyl)imidazole trifluoromethanesulfonic acid.
[0026] The preparation method is as follows: (1) 0.85 g of 1-butyl-3-(4-sulfobutyl)imidazole trifluoromethanesulfonic acid and 1.35 g of UiO-66-NH2 were mixed, ground for 2 h, heated to 70 ° C, and polymerized for 27 h. The product was extracted with acetonitrile, washed with methanol, centrifuged, and dried to obtain a composite; (2) adding 1 g of the complex into 50 mL of an aqueous solution containing 0.4 g of aluminum nitrate and 0.15 g of zinc nitrate, stirring for 40 min, centrifuging, washing, and drying to obtain an Al / Zn-loaded complex; (3) 1 g of the Al / Zn composite was added into 50 mL of an aqueous solution containing 0.04 g of cerium nitrate, immersed for 11 h, centrifuged, washed, and dried to obtain a catalyst.
[0027] Comparative Preparation Example 2 Compared with Preparation Example 3, the difference is that UiO-66-NH2 is replaced by nano-silicon dioxide (average particle size of 500 nm).
[0028] The preparation method is as follows: (1) 10 mmol of piperazine and 10.5 mmol of dibromo-p-xylene were mixed and added into 50 mL of acetonitrile. The mixture was heated under reflux for 27 h under nitrogen protection, centrifuged, washed and dried to obtain compound 1. (2) Add 2.1 g of compound 1 to 200 mL of ethanol, add 2.5 g of 1,3-propane sultone, heat to 60°C, stir to react for 3 h, centrifuge, wash, and dry to obtain compound 2; (3) Add 4.6 g of compound 2 to 200 mL of water, add 2.1 g of methanesulfonic acid, heat to 80 °C, stir to react for 8 h, remove the solvent under reduced pressure, wash with ether, and dry to obtain an ionic liquid; (4) 0.85 g of ionic liquid and 1.35 g of nano-silica were mixed, ground for 2 h, heated to 70 °C, polymerized for 27 h, extracted with acetonitrile, washed with methanol, centrifuged, and dried to obtain a composite; (5) Add 1 g of the complex into 50 mL of an aqueous solution containing 0.4 g of aluminum nitrate and 0.15 g of zinc nitrate, stir and react for 40 min, centrifuge, wash, and dry to obtain an Al / Zn-loaded complex; (6) 1 g of the Al / Zn composite was added into 50 mL of an aqueous solution containing 0.04 g of cerium nitrate, immersed for 11 h, centrifuged, washed, and dried to obtain a catalyst.
[0029] Comparative Preparation Example 3 Compared with Preparation Example 3, the difference is that aluminum nitrate is not added in step S6.
[0030] The details are as follows: S6. Add 1 g of the complex into 50 mL of an aqueous solution containing 0.55 g of zinc nitrate, stir and react for 40 min, centrifuge, wash, and dry to obtain a Zn-loaded complex.
[0031] Comparative Preparation Example 4 Compared with Preparation Example 3, the difference is that zinc nitrate is not added in step S6.
[0032] The details are as follows: S6. Add 1 g of the complex into 50 mL of an aqueous solution containing 0.55 g of aluminum nitrate, stir and react for 40 min, centrifuge, wash, and dry to obtain an Al-loaded complex.
[0033] Comparative Preparation Example 5 Compared with Preparation Example 3, the difference is that step S6 is not performed.
[0034] The details are as follows: S1. Add 1.55 g zirconium tetrachloride to 300 mL of a mixed solvent of N,N-dimethylformamide and acetic acid, add 1.3 g 2-aminoterephthalic acid, hydrothermally react at 125° C. for 22 h, centrifuge, wash, and dry to obtain UiO-66-NH2; the volume ratio of N,N-dimethylformamide to acetic acid in the mixed solvent of N,N-dimethylformamide and acetic acid is 35:3; S2. 10 mmol piperazine and 10.5 mmol dibromo-p-xylene were mixed and added to 50 mL acetonitrile. The mixture was heated under reflux for 27 h under nitrogen protection, centrifuged, washed, and dried to obtain compound 1. S3. 2.1 g of compound 1 was added to 200 mL of ethanol, and 2.5 g of 1,3-propane sultone was added, the temperature was raised to 60° C., the reaction was stirred for 3 h, centrifuged, washed, and dried to obtain compound 2; S4. Add 4.6 g of compound 2 to 200 mL of water, add 2.1 g of methanesulfonic acid, heat to 80 ° C, stir and react for 8 h, remove the solvent under reduced pressure, wash with ether, and dry to obtain an ionic liquid; S5. 0.85 g of ionic liquid and 1.35 g of UiO-66-NH2 were mixed, ground for 2 h, heated to 70 ° C, polymerized for 27 h, extracted with acetonitrile, washed with methanol, centrifuged, and dried to obtain a composite; S6. 1 g of the complex was added to 50 mL of an aqueous solution containing 0.04 g of cerium nitrate, immersed for 11 h, centrifuged, washed, and dried to obtain a catalyst.
[0035] Comparative Preparation Example 6 Compared with Preparation Example 3, the difference is that step S7 is not performed.
[0036] The details are as follows: S1. Add 1.55 g zirconium tetrachloride to 300 mL of a mixed solvent of N,N-dimethylformamide and acetic acid, add 1.3 g 2-aminoterephthalic acid, hydrothermally react at 125° C. for 22 h, centrifuge, wash, and dry to obtain UiO-66-NH2; the volume ratio of N,N-dimethylformamide to acetic acid in the mixed solvent of N,N-dimethylformamide and acetic acid is 35:3; S2. 10 mmol piperazine and 10.5 mmol dibromo-p-xylene were mixed and added to 50 mL acetonitrile. The mixture was heated under reflux for 27 h under nitrogen protection, centrifuged, washed, and dried to obtain compound 1. S3. 2.1 g of compound 1 was added to 200 mL of ethanol, and 2.5 g of 1,3-propane sultone was added, the temperature was raised to 60° C., the reaction was stirred for 3 h, centrifuged, washed, and dried to obtain compound 2; S4. Add 4.6 g of compound 2 to 200 mL of water, add 2.1 g of methanesulfonic acid, heat to 80 ° C, stir and react for 8 h, remove the solvent under reduced pressure, wash with ether, and dry to obtain an ionic liquid; S5. 0.85 g of ionic liquid and 1.35 g of UiO-66-NH2 were mixed, ground for 2 h, heated to 70 ° C, polymerized for 27 h, extracted with acetonitrile, washed with methanol, centrifuged, and dried to obtain a composite; S6. Add 1 g of the complex into 50 mL of an aqueous solution containing 0.4 g of aluminum nitrate and 0.15 g of zinc nitrate, stir and react for 40 min, centrifuge, wash, and dry to obtain an Al / Zn-loaded complex, which is a catalyst.
[0037] Comparative Preparation Example 7 Compared with Preparation Example 3, the difference is that steps S6 and S7 are not performed.
[0038] The details are as follows: S1. Add 1.55 g zirconium tetrachloride to 300 mL of a mixed solvent of N,N-dimethylformamide and acetic acid, add 1.3 g 2-aminoterephthalic acid, hydrothermally react at 125° C. for 22 h, centrifuge, wash, and dry to obtain UiO-66-NH2; the volume ratio of N,N-dimethylformamide to acetic acid in the mixed solvent of N,N-dimethylformamide and acetic acid is 35:3; S2. 10 mmol piperazine and 10.5 mmol dibromo-p-xylene were mixed and added to 50 mL acetonitrile. The mixture was heated under reflux for 27 h under nitrogen protection, centrifuged, washed, and dried to obtain compound 1. S3. 2.1 g of compound 1 was added to 200 mL of ethanol, and 2.5 g of 1,3-propane sultone was added, the temperature was raised to 60° C., the reaction was stirred for 3 h, centrifuged, washed, and dried to obtain compound 2; S4. Add 4.6 g of compound 2 to 200 mL of water, add 2.1 g of methanesulfonic acid, heat to 80 ° C, stir and react for 8 h, remove the solvent under reduced pressure, wash with ether, and dry to obtain an ionic liquid; S5. 0.85 g of ionic liquid and 1.35 g of UiO-66-NH2 were mixed, ground for 2 h, heated to 70°C, and polymerized for 27 h. The product was extracted with acetonitrile, washed with methanol, centrifuged, and dried to obtain a composite, which was the catalyst.
[0039] Test Example 1 The performance of the catalysts prepared in Preparation Examples 1-3 and Comparative Preparation Examples 1-7 was tested. The results are shown in Table 1.
[0040] The specific surface area and total pore volume of the catalyst were determined using a 3-FLEX 3500 multi-station high-throughput gas adsorption instrument.
[0041] Prepare 2mmol / L 4-nitroaniline indicator solution, weigh 1g of catalyst into a 10mL volumetric flask, draw 2mL of indicator solution into the above volumetric flask with a disposable syringe, and make up to volume with deionized water to prepare the test solution. Use an ultraviolet spectrophotometer to scan the full wavelength of the test solution, calculate its Hammett acidity function, and then obtain the acidity ( H 0) value.
[0042] Table 1 ; It can be seen from the above table that the catalysts prepared in Preparation Examples 1-3 of the present invention have larger specific surface area, total pore volume and suitable acidity. Example 1
[0043] The present embodiment provides a method for producing LC-grade diethyltoluenediamine, comprising the following steps: Under nitrogen protection, toluenediamine and the catalyst prepared in Preparation Example 1 were mixed, the amount of the catalyst added was 0.5wt% of toluenediamine, the temperature was raised to 160°C, and stirred, and ethylene and composite gas were introduced at the same time, the volume ratio of ethylene to composite gas was 1:1, the pressure was 6MPa, and the temperature was kept under pressure for 2h, the temperature was lowered, the pressure was released, the material was discharged, and the liquid was refined to obtain LC grade diethyltoluenediamine; The composite gas includes nitrogen, hydrogen chloride and trimethylamine in a volume ratio of 7:3:1. Example 2
[0044] The present embodiment provides a method for producing LC-grade diethyltoluenediamine, comprising the following steps: Under nitrogen protection, toluenediamine and the catalyst prepared in Preparation Example 2 were mixed, the amount of the catalyst added was 1.5wt% of toluenediamine, the temperature was raised to 180°C, stirred, and ethylene and composite gas were introduced at the same time, the volume ratio of ethylene to composite gas was 1:1, the pressure was 7MPa, the temperature was kept and pressurized for 4h, the temperature was lowered, the pressure was released, the material was discharged, and the liquid was refined to obtain LC grade diethyltoluenediamine; The composite gas includes nitrogen, hydrogen chloride and trimethylamine in a volume ratio of 10:5:3. Example 3
[0045] The present embodiment provides a method for producing LC-grade diethyltoluenediamine, comprising the following steps: Under nitrogen protection, toluenediamine and the catalyst prepared in Preparation Example 3 were mixed, the amount of the catalyst added was 1wt% of toluenediamine, the temperature was raised to 170°C, and stirred, and ethylene and composite gas were introduced at the same time, the volume ratio of ethylene to composite gas was 1:1, the pressure was 6.5MPa, and the temperature was kept under pressure for 3h, the temperature was lowered, the pressure was released, the material was discharged, and the liquid was refined to obtain LC grade diethyltoluenediamine; The composite gas includes nitrogen, hydrogen chloride and trimethylamine in a volume ratio of 8:4:2.
[0046] Comparative Examples 1-7 Compared with Example 3, the difference is that the catalysts are prepared in sequence from Comparative Preparation Examples 1-7.
[0047] Test Example 2 The reactions in Examples 1-3 and Comparative Examples 1-7 were evaluated and the results are shown in Table 2.
[0048] Table 2 ; It can be seen from the above table that the conversion rate of toluenediamine in the reaction of Examples 1-3 of the present invention is high, and the yield of diethyltoluenediamine is high.
[0049] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for producing LC-grade diethyltoluenediamine, characterized in that: The following steps are involved: Under the protection of inert gas, toluenediamine and a catalyst are mixed, heated and stirred, and ethylene and a composite gas are introduced at the same time, the volume ratio of ethylene to the composite gas is 1:1, the reaction is carried out under heat preservation and pressure, the pressure of the heat preservation and pressure reaction is 6-7MPa, the temperature is reduced, the pressure is released, the material is discharged, and the liquid is refined to obtain LC-grade diethyltoluenediamine; the catalyst is a product of the reaction of piperazine and dibromo-p-xylene reacted with 1,3-propane sultone, methane sulfonic acid is added to obtain an ionic liquid, which is mixed with UiO-66-NH2, complexed with Al and Zn ions, and impregnated with a cerium salt solution to obtain a catalyst, and the added amount of the catalyst is 0.5-10wt% of the toluenediamine; the composite gas includes an inert gas, a protonic acid gas and an ammonia gas.
2. The production method according to claim 1, characterized in that The temperature is raised to 160-180°C for 2-4 hours. The composite gas is composed of an inert gas, a protonic acid gas and an ammonia gas in a volume ratio of 7-10:3-5:1-3. The protonic acid gas is selected from at least one of hydrogen fluoride, hydrogen chloride, hydrogen bromide, hydrogen iodide, hydrogen sulfide and fluorosilicic acid gas. The ammonia gas is selected from at least one of ammonia, monomethylamine, dimethylamine, trimethylamine and triethylamine gas.
3. The production method according to claim 1, characterized in that The addition amount of the catalyst is 0.5-1.5wt% of toluenediamine, and the preparation method of the catalyst is as follows: S1. Adding zirconium tetrachloride to a mixed solvent of N,N-dimethylformamide and acetic acid, adding 2-aminoterephthalic acid, hydrothermally reacting, centrifuging, washing, and drying to obtain UiO-66-NH2; S2. piperazine and dibromo-p-xylene were mixed and added to acetonitrile, and the mixture was heated under reflux under inert gas protection, centrifuged, washed, and dried to obtain compound 1; S3. Compound 1 is added to a solvent, 1,3-propane sultone is added, the temperature is raised, the reaction is performed by centrifugation, washing, and drying to obtain compound 2; S4. Compound 2 was added to water, methanesulfonic acid was added, the reaction was heated and stirred, the solvent was removed under reduced pressure, washed with ether, and dried to obtain an ionic liquid; S5. The ionic liquid and UiO-66-NH2 were mixed, ground, heated for polymerization reaction, the product was extracted with acetonitrile, washed with methanol, centrifuged, and dried to obtain a composite; S6. The complex is added to an aqueous solution of aluminum salt and zinc salt, the reaction is stirred, centrifuged, washed, and dried to obtain an Al / Zn-loaded complex; S7. Adding the Al / Zn composite to an aqueous solution of cerium salt, impregnating, centrifuging, washing, and drying to obtain a catalyst.
4. The production method according to claim 3, characterized in that: In step S1, the volume ratio of N,N-dimethylformamide to acetic acid in the mixed solvent of N,N-dimethylformamide and acetic acid is 35:2-4, the mass ratio of zirconium tetrachloride to 2-aminoterephthalic acid is 14-17:12-14, the temperature of the hydrothermal reaction is 120-130° C., and the time is 20-24 hours.
5. The production method according to claim 3, characterized in that: In step S2, the molar ratio of piperazine to dibromoparaxylene is 1:1-1.1, and the heating reflux reaction time is 24-30 hours.
6. The production method according to claim 3, characterized in that: In step S3, the mass ratio of compound 1 to 1,3-propane sultone is 20-22:24-26, the temperature of the temperature-raising reaction is 55-65° C., and the time is 2-4 hours.
7. The production method according to claim 3, characterized in that: In step S4, the mass ratio of compound 2 to methanesulfonic acid is 45-47:20-22, the temperature of the heating and stirring reaction is 75-85° C., and the time is 7-10 h.
8. The production method according to claim 3, characterized in that: In step S5, the mass ratio of the ionic liquid to UiO-66-NH2 is 7-10:12-15, the grinding time is 1-3 hours, and the temperature of the heating polymerization reaction is 65-75°C for 24-30 hours.
9. The production method according to claim 3, characterized in that: In step S6, the mass ratio of the composite, the aluminum salt and the zinc salt is 10:3-5:1-2, the aluminum salt is selected from at least one of aluminum sulfate and aluminum nitrate, the zinc salt is selected from at least one of zinc chloride, zinc sulfate and zinc nitrate, and the stirring reaction time is 30-50min; in step S7, the mass ratio of the Al / Zn composite and the cerium salt is 100:3-5, the impregnation time is 10-12h, and the cerium salt is cerium chloride or cerium nitrate.
Citation Information
Patent Citations
A method for synthesizing diethyltoluenediamine
CN106083605B
Method for synthesizing diethyltoluenediamine
CN106083605A
Synthesis method of diethyltoluenediamine
CN106946714A
Preparation method for composite adsorbent of ionic liquid and metal organic framework and application of composite adsorbent
CN107638870A
Porous composite material for catalytic synthesis of propylene carbonate and preparation method thereof
CN112827510A
Cited By
Synthesis method of high-yield diethyl toluenediamine
CN122102921A